Reading in a second language moving from theory to practice - Grabe, William 1950- (Cambridge University Press, 2022)
Understanding reading abilities and their development is fundamental for language comprehension and human cognition. Now in its second edition, this book draws on research from multiple disciplines to explain reading abilities in both L1 and L2, and shows how this research can be applied in practice in order to support reading development. Research into reading has progressed a great deal since the first edition was published, so this edition has been completely updated and revised, in order to reflect these advances. All chapters present updated research studies, and completely new chapters are included on the neurocognition of reading, reading-writing relationships, and digital reading. If you want to know how reading works, no matter the language(s) involved, as well as how it can be taught effectively, this book provides a persuasive research foundation and many practical insights. It is essential reading for academic researchers and students in Applied Linguistics and TESOL.
Keywords: Vorlesung; Lehren; Lesefähigkeit; Studium; Sprache; Fremdsprachenunterricht; Leseunterricht; Fremdsprachenlernen